Desenvolvimento de ensaio imunoquímico para detecção de doping com eritropoetina - Collares, Thais Farias (2013)
The history of sports competition has been related to the use of methods for physical training associated with physiological methods to increase athlete performance. Ethical issues involving the high performance sport and doping are confused with the history of competitive sports. The World Anti - Doping Agency (WADA) prohibits the use of substances or methods to artificially increase sports performance. Currently, 258 substances are listed by WADA and athletes around the world are subjected to tests proving the non-use of doping. EPO is a glycoprotein hormone that has as its main physiological effect induction of erythropoiesis and thereby improving the capacity to transport oxygen in the blood. For these reason EPO has been included in WADA list. The analytical differentiation of endogenous erythropoietin from its recombinant counterpart, using isoelectric focusing and double blotting is a milestone in the detection of doping with recombinant erythropoietin. However, several analogs of the original recombinant EPO are not easily detectable by standard IEF method, requiring the development of alternatives for the detection of doping. In order to improve the current methods of EPO detection, monoclonal and polyclonal antibodies against EPO were obtained and used in various techniques for detection of EPO in biological samples. However, the specificity of these antibodies has been quite controversial and discussed. Therefore, it is necessary to obtain antibodies capable of reacting specifically with the EPO. In this study, rHuEPO was inoculated in New Zealand rabbits to generate a polyclonal antibody (pAb anti-rHuEPO). The pAb was characterized for its potential in detecting rHuEPO using different approaches. The pAb anti- rHuEPO identified the expression of recombinant protein in eukaryotic cells and was able to detect rHuEPO in a suspension at 0.1 μg/mL, showing its potential as a tool for detection of doping by rHuEPO.